Evidence for an ¹⁸O-depleted mantle plume from contrasting ¹⁸O/¹⁶O ratios of back-arc lavas from the Manus Basin and Mariana Trough. - Macpherson, C.G; Hilton, D.R; Mattey, D.P; Sinton, J.M (Earth and Planetary Science Letters, 2025)
no abstract